What does it feel like? : [large type] a novel - Kinsella, Sophie (Thorndike Press large print top shelf., 2024)
"Eve is a successful novelist who wakes up one day in a hospital bed with no memory of how she got there. Her husband, never far from her side, explains that she has had an operation to remove the large, malignant tumor growing in her brain. As Eve learns to walk, talk, and write again-and as she wrestles with her diagnosis, and how and when to explain it to her beloved children-she begins to recall what's most important to her: long walks with her husband's hand clasped firmly around her own, family game nights, and always buying that dress when she sees it. Recounted in brief anecdotes, each one is an attempt to answer the type of impossible questions recognizable to anyone navigating the labyrinth of grief. This short, extraordinary novel is a celebration of life, shot through with warmth and humor-it will both break your heart and put it back together again"--